Overexpression of miR-21 in stem cells improves ovarian structure and function in rats with chemotherapy-induced ovarian damage by targeting PDCD4 and PTEN to inhibit granulosa cell apoptosis - Fu, Xiafei; He, Yuanli; Wang, Xuefeng; Peng, Dongxian; Chen, Xiaoying; Li, Xinran; Wang, Qing (Stem cell research & therapy, 2017)
Chemotherapy-induced premature ovarian failure (POF) is a severe complication affecting tumor patients at a childbearing age. Mesenchymal stem cells (MSCs) can partially restore the ovarian structure and function damaged by chemotherapy. miR-21 is a microRNA that can regulate cell apoptosis. This study discusses the repair effect and mechanism of MSCs overexpressing miR-21 on chemotherapy-induced POF. Rat MSCs and granulosa cells (GCs) were isolated in vitro. MSCs were transfected with miR-21 lentiviral vector (LV-miR-21) to obtain MSCs stably expressing miR-21 (miR-21-MSCs). The microenvironment of an ovary receiving chemotherapy was mimicked by adding phosphamide mustard (PM) into the cellular culture medium. The apoptosis rate and the mRNA and protein expression of target genes PTEN and PDCD4 were detected in MSCs. Apoptosis was induced by adding PM into the culture medium for GCs, which were cocultured with miR-21-MSCs. The apoptosis rate and the mRNA and protein expression of PTEN and PDCD4 were detected. The chemotherapy-induced POF model was built into rats by intraperitoneal cyclophosphamide injection. miR-21-MSCs were transplanted into the bilateral ovary. The rats were sacrificed at 15, 30, 45, and 60 days after the last injection. The ovarian weights, follicle count, estrous cycle, and sex hormone levels (estradiol (E2) and follicle-stimulating hormone (FSH)) were detected. Apoptosis of GCs was determined by TUNEL assay. The miR-21 and mRNA and protein expression of PTEN and PDCD4 were determined. The apoptosis decreased in MSCs transfected with miR-21. The mRNA and protein expression of target genes PTEN and PDCD4 was downregulated. GCs cocultured with miR-21-MSCs showed a decreased apoptosis, an upregulation of miR-21, and a downregulation of PTEN and PDCD4. Following the injection of miR-21-MSCs, the ovarian weight and follicle counts increased; E levels increased while FSH levels decreased, with less severe apoptosis of GCs. The miR-21 expression in the ovaries was upregulated, while the mRNA expression and protein expression of PTEN and PDCD4 were downregulated. Overexpression of miR-21 in MSCs promoted efficacy against chemotherapy-induced POF and its improvement of the repair effect was related to the inhibition of GC apoptosis by targeting PTEN and PDCD4.